Effect of edible mushroom antioxidants on the oxidative stability and quality of meat products: advances and research trends through a systematic and bibliometric review (Scientia Agropecuaria, 2026)
Lipid and protein oxidation remain key challenges that limit the technological, sensory, and nutritional quality of meat products. This systematic review compiles evidence published from 2011 to 2025 on the antioxidant properties of edible mushrooms and their ability to reduce oxidative breakdown in meat matrices. Searches were performed in Scopus and Web of Science, yielding 821 records, of which 60 met the inclusion criteria in accordance with PRISMA guidelines. Across studies, Pleurotus ostreatus, Agaricus bisporus, Flammulina velutipes, and Hericium erinaceus consistently showed significant reductions in lipid peroxidation (20% – 40% decreases in TBARS) and moderate reductions in protein carbonylation. These antioxidant effects were mechanistically linked to synergistic interactions among phenolic acids, ergothioneine, flavonoids, and β-glucans. Additional benefits included improvements in color stability, water-holding capacity, and fiber and amino acid profiles. However, substantial variability was present across different species, extraction methods, and inclusion levels. Evidence supporting the inhibition of protein oxidation remains limited, bioaccessibility data are scarce, and standardization of mushroom-based meat products is lacking. Overall, edible mushrooms show strong potential as multifunctional, clean-label antioxidant systems; nonetheless, more mechanistic, quantitative, and digestion-focused studies are needed for industrial-scale application. These findings indicate promising applications in clean-label meat reformulation, although industrial validation and standardized reporting of oxidative markers remain required.